THE POTENCY OF LUBUK LARANGAN JORONG LANDAI AS LOCAL WISDOM BASED ECOTOURISM AREA - Netri Rosnita; Muhammad Fauzi; Adriman Adriman (Fakultas Perikanan dan Kelautan, Universitas Riau, 2019)
This study aimed to understand the local wisdom and the feasibility of the area as an ecological tourism object. The research has been carried out from February to April 2018. Water quality data collection was carried out four times (once/two weeks), while interviews and questionnaires were distributed prior to environmental data collection. Water samples were taken from three stations, while local wisdom and ecotourism data were collected through the interview and questionnaires. The results showed that the shown that the community used to maintains the Jorong Landai ecosystem by applying regulations for fish capture and fish harvesting system. The water quality parameter in the Lubuk Larangan was as follows: the temperature was 21-22 0C, the current speed was 0.04-0.5 m/s, water depth was 44-82 cm, dissolved oxygen was 4.46-5.78 Mg/L and pH was 6. The value ecotourism of the feasibility index was as follows: attractiveness was 945, accessibility was 587.5, the social-economic condition was 462.5, accommodation was 0, infrastructure was 180 and the availability of clean water was 870 (total value was 3,045). This value indicates that the Lubuk Larangan Jorong Landai can be categorized as appropriate for ecotourism object.